Occlusion Concept for Fabricating Complete Denture (Literature Review) - Sania Mahira, Cherryl; Jihan Aribah; Hafizh Naufal Aldhito; Rais, Sri Wahyuningsih; Febriani (Sriwijaya Journal of Dentistry, 2024)
Introduction: Patients with full edentulism experience difficulties in chewing food, thus requiring complete dentures aiming to restore the missing teeth, other structures, and the patient's masticatory efficiency. Complete denture fabrication requires retention, stability and support of the remaining tissues. This is influenced by the selection of a good occlusion concept. There are several types of occlusion concepts such as Bilateral Balanced Occlusion (BBO), Lingualized Occlusion (LO) and Canine Guided Occlusion (CGO). Purpose: The aim of this literature review was to determine the use of the ideal occlusion concept in complete dentures according to the patient's condition. Methods: Literature was selected using the databases PubMed, Science Direct, Wiley Online Library, Elsevier, and Google Scholar from January 2007 to December 2022. Articles that met the inclusion and exclusion criteria were assessed using the Cochrane Collaboration Tool for bias assessment and summarized to obtain data on occlusion concept for fabricating full denture. Results: Fourteen randomized controlled trial journals discussing about three occlusion concepts that are BBO, LO and CGO were included in this literature review. Occlusal concept should be used according to the indication and condition of the patient. Conclusion: Occlusion concepts give positive impact if chosen wisely according to the patient's condition.